VIRTUAL CONSERVATION-RESTORATION VS. ACTUAL CONSERVATION-RESTORATION IN THE CONSERVATION OF FRAGMENTARY ARTEFACTS: THE CASE STUDY FRESCOES FROM SYBARIS - COPIA (ITALY) - Muca, Sokol (Protection of Cultural Heritage, 2019)
This article discusses the role that new digital technologies play on conservation-restoration of fragmentary artefacts. Above all, the use of these tools is essential in case the artefacts have lost the formal unity and reach us without documentation concerning their original position, as in the case of the Roman frescoes from Sybaris, object of this study. The creation of virtual models proves as fundamental for the material and formal recomposition of the artefacts, especially in the creation of a new support and display choices. This last aspect required an analysis on the effects that virtual reconstructions and augmented reality have on visitors.